Emerging Trends in Neuropalliative Care: A Palliative Approach to Epilepsy and Seizure Management in Adults - Willert, Anna-Christin; Kowski, Alexander Bernhard (Seminars in Neurology, 2024)
Management of severe (drug-resistant) epilepsy and epilepsy in other serious illnesses is multidimensional and requires consideration of both physical symptoms and psychosocial distress that require individualized treatment. Palliative care offers a holistic approach to disease that focuses on all dimensions of suffering to maintain quality of life. Integration of a palliative care mind- and skillset in the management of severe epilepsy and epilepsy in other serious illnesses can provide person-centered care and support for families and caregivers.
Keywords: epilepsy; seizures; neuropalliative care